The new ecology : rethinking a science for the Anthropocene - Schmitz, Oswald J. (Princeton University Press, 2018)
Our species has transitioned from being one among millions on Earth to the species that is single-handedly transforming the entire planet to suit its own needs. In order to meet the daunting challenges of environmental sustainability in this epoch of human domination - known as the Anthropocene - ecologists have begun to think differently about the interdependencies between humans and the natural world. This work provides the best available introduction to what this new ecology is all about - and why it matters more than ever before.